2019
DOI: 10.1111/jcmm.14602
|View full text |Cite
|
Sign up to set email alerts
|

Production of bioactive recombinant human myeloid‐derived growth factor in Escherichia coli and its mechanism on vascular endothelial cell proliferation

Abstract: Myeloid‐derived growth factor (MYDGF) is a novel protein secreted by bone marrow cells that features important physiological functions. In recent years, MYDGF has gained considerable interest due to their extensive beneficial effect on cardiac repair and protects cardiomyocytes from cell death. However, its precise molecular mechanisms have not been well elucidated. The purpose of this study was to produce sufficient amount of biologically active recombinant human (rh) MYDGF more economically and effectively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 40 publications
1
10
1
Order By: Relevance
“…C19orf10 activated the PKA/GSK-3β/β-catenin and MAPK/MEK/ERK pathways in diabetic mice and STC-1 cells ( 24 ). It has been reported that recombinant human C19orf10 could regulate human coronary artery endothelial cell proliferation and survival by MAPK/STAT3 and the cyclin D1 signaling pathway ( 25 ). So far the underlying mechanism of C19orf10 regulated Akt related pathways is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…C19orf10 activated the PKA/GSK-3β/β-catenin and MAPK/MEK/ERK pathways in diabetic mice and STC-1 cells ( 24 ). It has been reported that recombinant human C19orf10 could regulate human coronary artery endothelial cell proliferation and survival by MAPK/STAT3 and the cyclin D1 signaling pathway ( 25 ). So far the underlying mechanism of C19orf10 regulated Akt related pathways is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Mydgf has been reported to play a crucial role during cardiac repair, such as promoting angiogenesis and inhibiting CM apoptosis 18 , 19 , 27 . Our results display that the proliferation of ECs and FBs was not significantly induced by Mydgf after neonatal cardiac injury, suggesting that Mydgf-induced CM proliferation is the major factor for neonatal heart regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Our results display that the proliferation of ECs and FBs was not significantly induced by Mydgf after neonatal cardiac injury, suggesting that Mydgf-induced CM proliferation is the major factor for neonatal heart regeneration. It has been reported that Mydgf promotes EC proliferation through phosphorylation of STAT3 on S727 and stimulates STAT3 transcriptional activity 18 , 19 . Our results show that STAT3 is not be activated in Mydgf-treated CMs, indicating that STAT3 signaling is not involved in Mydgf-indcued CM proliferation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MYDGF was proven to be a promising biotherapeutic prototypic drug for acute myocardial infarction (MI), because it promotes cell survival and stimulates angiogenesis after ischemia reperfusion (Korf-Klingebiel et al, 2015). The accumulating evidence confirms MYDGF's efficacy for cell protection and tissue repair (Wang, Li, Feng, et al, 2020;Yuan et al, 2019;Zhao et al, 2019). The function of MYDGF was explored in subsequent studies with beneficial indications for diseases such as type 2 diabetes or diabetic kidney disease (He et al, 2020;Wang, Li, Guo, et al, 2020).…”
Section: Introductionmentioning
confidence: 99%